2006
DOI: 10.1111/j.1440-1789.2006.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary rhabdoid tumor of the brain in an adult

Abstract: Rhabdoid tumor (RT) is an uncommon childhood neoplasm that typically arises within the kidney. It is characterized by an aggressive clinical course. Since its description in 1978, several cases of primary extrarenal RT, including a CNS localization, have been reported. The first case in the CNS was reported in 1985 and was defined as "rhabdoid tumor" initially, and was classified as grade IV in the most recent classification of the World Health Organization under the term of "atypical teratoid/rhabdoid tumor".… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 17 publications
2
11
0
2
Order By: Relevance
“…AT/RT was first recognized as a malignant intracranial rhabdoid tumor in an adult patient in 1992 by Horn et al 30 From then on, approximately 30 cases of adult AT/RT have been reported. [18][19][20][21][22][23][24][25][26][27][28][29][30] In contrast to the pediatric neoplasm, most adult CNS rhabdoid tumors are supratentorial, with only 3 tumors located in the cerebellum and 2 in the spinal cord. Most cases were diagnosed on the basis of characteristic histologic and immunohistochemical features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AT/RT was first recognized as a malignant intracranial rhabdoid tumor in an adult patient in 1992 by Horn et al 30 From then on, approximately 30 cases of adult AT/RT have been reported. [18][19][20][21][22][23][24][25][26][27][28][29][30] In contrast to the pediatric neoplasm, most adult CNS rhabdoid tumors are supratentorial, with only 3 tumors located in the cerebellum and 2 in the spinal cord. Most cases were diagnosed on the basis of characteristic histologic and immunohistochemical features.…”
Section: Discussionmentioning
confidence: 99%
“…17 To our knowledge, only 29 cases of primary AT/RT of the CNS in adults have been reported (On-line Table). [18][19][20][21][22][23][24][25][26][27][28][29][30] The On-line Table summarizes the clinical and imaging data from our patients and from those in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,25) Only 25 adult cases of cerebral RTs, including AT/RTs and malignant RTs, have been reported. 1,2,8,10,[13][14][15]19,23,24,27,31,32,38,39,41,42,45) Only 6 cases of epithelioid glioblastoma with a rhabdoid component have been reported. 16,26,28,47) However, the World Health Organization (WHO) Classification of Tumours of the Central Nervous System classifies AT/RTs as embryonal tumors, but does not list malignant RT and rhabdoid glioblastoma as distinct categories.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,10,13,15,17,18 Only single cases have been reported in adults. [22][23][24][25][26][27][28][29][30][31][32] Several large, hospital-based series established an atypical teratoid/rhabdoid tumor prevalence of 1% to 2% among pediatric brain tumors, 8,[33][34][35] but population-based data on the incidence of atypical teratoid/rhabdoid tumors in children are not yet available. However, such data provide important insights into the burden of disease and might contribute to patient care.…”
mentioning
confidence: 99%